Relapsing subcutaneous nodules of the penis in a pediatric patient - Andrea Sechi; Emanuele Stefano Giovanni d'Amore; Luigi Naldi; Massimo Bellettato; Marco May Lee; Mario Cutrone (PAGEPress Publications, 2023)
A 14-year-old boy presented with a history of non-tender, subcutaneous coalescing nodules located on the ventral-lateral aspects of the penis shaft for one year. Laboratory investigations for blood count and autoimmunity were within normal limits. Complete excision was performed, and on histology, the dermis showed necrobiotic material composed of altered collagen bundles, surrounded by a palisade of histiocytes and scattered lymphocytes, thus allowing a diagnosis of subcutaneous granuloma annulare. Only 18 published cases reported penile granuloma annulare. Medical management was advocated in 7/18 cases, either as a first-line or adjuvant therapy where surgery was not radical. Three patients received high-potency local steroids: two cases underwent adjuvant sessions of intralesional triamcinolone, and one patient received pentoxifylline orally. Surgery should be considered a second-line option since 5/8 of treated cases eventually recurred. The pentoxifylline-treated case witnessed a relapse after drug discontinuation, while topical steroids lead to complete recovery without relapses.